Edward Hopper : vision of reality. - Kranzfelder, Ivo, 1958- (Köln, Germany : Benedikt Taschen, 1995)
Life and work of Edward Hopper.
Keywords: Hopper, Edward, -- 1882-1967.; Painters, American -- Biography